Recruitment Pattern Graduates from Malaysian Technical University - Sulong, Muhammad Suhaimi; Muhamad Hanafi, Nurfirdawati; Awang, Halizah; Mohamed Yusof, Anizam; Mohd Faiz, Nur Sofurah (Online Journal for TVET Practitioners, 2023)
Recruitment is a process of identifying individuals who have the potential to create a quality staff that will ensure the achievement of a company’s goals and mission. Many employers are interested in recruiting capable graduates. However, there are still employers who do not offer a salary equivalent to the student’s qualifications. Accordingly, this study aims to determine the recruitment pattern for Universiti Tun Hussein Onn Malaysia (UTHM) graduates from 2015 until 2020. It identifies graduates of UTHM, a public technical university who receive salaries equivalent to their qualifications at the Diploma level. It also aims to identify employers who consistently hire UTHM graduates from the designated years. This empirical study analyzed raw data from the Graduate Tracer Study online system administered by the Ministry of Higher Education Malaysia. The respondents consisted of 1302 diploma graduates at UTHM. The results of the study show that only 32% of graduates receive a salary commensurate with their diploma qualification. This shows a high mismatch between the job salaries and qualifications of graduates. Further results also found that there are 43 companies consistently recruiting UTHM Diploma Graduates from 2015 to 2020. Attentively, JST Connector (Malaysia) Sdn. Bhd is the most consistent company in recruiting UTHM Diploma graduates with a total of 15 employees in that period.